1985
DOI: 10.1039/c39850000347
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and structural characterization of binuclear µ-oxo-di-µ-acetato bridged complexes of manganese(III). Analogues of the di-iron(III) centre in hemerythrin

Abstract: The complexes [ L2 M n11I 2 ( 1.1-0 ) ( p-M eC02 12] ( C 104)2, ( 1 1, a n d [ L'2 M n11I 2 ( p-0 ) ( p-M eC O2 1 2] (C I 04) 2-H 20, (21, where L and L' represent the cyclic triamines 1,4,7-triazacyclononane and (N,N',N"-trimethyl-1,4,7-triazacyclononane, have been synthesized from Mn( MeC02)3.2H20 in water-ethanol mixtures; characterization by X-ray crystallography showed that both complexes contain a p-0x0-di-p-acetato-metal(l11) core, as found in hemerythrin, and therefore these complexes may have bioinorg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
120
0
2

Year Published

1988
1988
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(130 citation statements)
references
References 0 publications
8
120
0
2
Order By: Relevance
“…The global coordination number for this vector (Nisotropic) was 0.41 2 0.02, or two Mn -Mn interactions at this distance. This is consistent with the presence of one mono-p-oxo and mono-or di-carboxylato bridged moiety per tetramer Wieghardt et al, 1983Wieghardt et al, , 1985Sheats et al, 1987). Inclusion of a second shell of Mn-Ca decreased the fit error by a factor of 2 to 3, depending on the data set, but the results were not conkistent enough to confirm the requirement for this shell.…”
Section: Peak 1 1supporting
confidence: 64%
“…The global coordination number for this vector (Nisotropic) was 0.41 2 0.02, or two Mn -Mn interactions at this distance. This is consistent with the presence of one mono-p-oxo and mono-or di-carboxylato bridged moiety per tetramer Wieghardt et al, 1983Wieghardt et al, , 1985Sheats et al, 1987). Inclusion of a second shell of Mn-Ca decreased the fit error by a factor of 2 to 3, depending on the data set, but the results were not conkistent enough to confirm the requirement for this shell.…”
Section: Peak 1 1supporting
confidence: 64%
“…Iron and manganese are exchangeable in calf thymus ribonucleotide reductase in vitro [29]. Structurally related Me(1II) (p-0x0)-(p-carboxylato)2Me(III) complexes have been synthesized with both metals to model metalloprotein centers [31,321. The light absorption between 400nm and 700nm of our new manganese enzyme (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, neither of these scenarios would predict that the first-shell Fourier peak would be more intense in the Mn 2 (III,III) complex than the Mn 2 (III,IV) complex. In fact, a similar mono-µ-oxo Mn 2 (III,III) complex with tacn (triazacyclononane) terminal ligands has been synthesized by Wieghardt et al 304 and it was shown by DeRose et al 72 to have a significantly reduced amplitude of the first-and second-shell Fourier peaks relative to the S 1 state of PS II. Because single crystals have been obtained of all three of these complexes from…”
Section: Exafsmentioning
confidence: 99%